Inequality in the distribution of income in Singapore : a theil decomposition analysis - Zhang, Jinxiong (2012)
Income inequality has continued to worsen in Singapore, with the country’s Gini coefficient ranked second highest behind only Hong Kong among developed countries according to a 2009 United Nations Report. As social tension begins to surface, which is evident from the watershed General Election in 2011, it is essential to discover the subgroups of population that are most affected by income inequality so as to allow effective policymaking to address this predicament. This paper examines income inequality in its entirety in Singapore and provides possible improvements and recommendations to existing policies. In order to get a greater appreciation of income inequality in Singapore, we have analysed the trend of Gini coefficient in the country for the past 40 years. Using Theil index, which is able to decompose income inequality into the different subgroups of population, this paper identifies and analyzes the extent that factors such as industry, age, education, and race contributes to income inequality in Singapore. Our empirical results show that, in terms of age, the elderly age group contributes most to income inequality while in terms of industry, the construction sector in particular contributed significantly to the income inequality as compared to other sectors. Potential policy recommendations such as redistribution of income and increasing labour productivity should be targeted to alleviate income inequality, allowing for a more inclusive society.